2014
DOI: 10.1016/j.ehb.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimating male and female height inequality

Abstract: This study investigates the coefficient of variation (CV) of height of males and females as a measure of inequality. We have collected a data set on corresponding male and female height CVs from 124 populations, spanning the period between the 1840s and 1980s. The results suggest that the R² between the two CVs is 0.39, with the male CV being greater, indicating higher plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
0
16
0
4
Order By: Relevance
“…It is evident that coefficient of variation (CV) is a widely used and robust index for measuring inequality [28] as it does not increase with average height like standard deviation (SD). Figures 5 and 6 show that CVs of rural subjects are higher than that of urban subjects in most age groups except 17–18 years old boys and 15–18 years old girls where rural CVs are similar to urban CVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that coefficient of variation (CV) is a widely used and robust index for measuring inequality [28] as it does not increase with average height like standard deviation (SD). Figures 5 and 6 show that CVs of rural subjects are higher than that of urban subjects in most age groups except 17–18 years old boys and 15–18 years old girls where rural CVs are similar to urban CVs.…”
Section: Discussionmentioning
confidence: 99%
“…T-test was used to analyze the differences in heights between urban and rural, eastern and western regions and Shanghai and Guizhou by the SPSS (PASW Statistics 18, SPSS Inc. Chicago, IL). To compare height equalities within urban and rural areas, coefficient of variation(CV) of height was computed in each sex-age group with the equation [28]: CV = (σ/μ)*100(σ and μ mean standard deviation and mean stature respectively).…”
Section: Methodsmentioning
confidence: 99%
“…They also found that women were taller than men in those societies, that the women's contribution to food production was greater than that of the men resulting in improvement of females' nutritional status in these societies. Other factors which have been reported to influence the M/F height ratio in preindustrial societies are probably the male and female division in agricultural tasks (30). The women in these societies usually were engaged in cattle farming and garden work, thereby increasing their "advantage of proximity" to milk and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors which have been reported to influence the M/F height ratio in preindustrial societies are probably the male and female division in agricultural tasks ( 30 ). The women in these societies usually were engaged in cattle farming and garden work, thereby increasing their “advantage of proximity” to milk and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baten (2000) documented a range of 3.63-3.83 for Bavarian conscripts born during 1815-1965 and Ayuda and Puche-Gil (2014), a range of 3.62-3.84 for Valencian male birth cohorts between 1880-1960. In addition, Blum (2014) reported that the SD of the CV for 124 populations was only 0.38. Table 1 shows the SD and CV statistics of the data.…”
Section: Discussionmentioning
confidence: 99%